Temperature effect on Brazilian soybean yields, and farmers’ responses - Daniel S. Silva; Eugenio Y. Arima; Tiago N. P. dos Reis; Ludmila Rattis (International Journal of Agricultural Sustainability, 2023)
Brazil is one of the largest suppliers of commodities in the world, partly due to the agricultural expansion in the Cerrado biome that began in the 1970s. However, as areas with better soil and climate for agriculture become scarce, farmers advanced to marginal lands, where precipitation is less reliable for rainfed crops. The overall goal of this paper is to investigate the implications of occupying drier areas in the Cerrado biome, which are likely to become more so in the future. We estimated the effect of temperature and precipitation on soybean yields (kg/ha) using panel data regression at the municipal level, from 1980 to 2016, and at the farm-level in a subset region known as Matopiba. Our analysis estimated a reduction of 6% in soybean yield for each 1°C increase in temperature. According to interviewed farmers, the consequences of the recent droughts include land concentration and increased indebtedness. Based on historical observations, agricultural technologies do not provide adaptation to extreme heat and created a dependency on capital availability for investments in irrigation, raising questions about the future sustainability of this capital-intensive agricultural system if breakthroughs in adaptation do not occur.